The 2015 refugee inflow and concerns over immigration - Katia Gallegos Torres (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
How did the large asylum-seeker inflow to Germany in 2015 affect concerns about immigration? Using individual-level panel data for the years 2012-2018, I show that after 2015 concerns about immigration increased by about 21 pp. and support for extreme right-wing parties by about 1.7 pp. These trends show considerable heterogeneity for different demographic groups. Using a policy that allocates asylum- seekers to districts I identify the effect of exposure to asylum-seekers. In line with the contact hypothesis, living in a high refugee migration district reduced concerns about immigration by 3 pp. The effect appears larger for right- leaning respondents but is otherwise similar across demographic groups.
Keywords: J15; D72; P16; R23; 330; immigration; refugees; attitudes; concerns about immigration